Schoolteachers' Resilience Does but Self-Efficacy Does Not Mediate the Influence of Stress and Anxiety Due to the COVID-19 Pandemic on Depression and Subjective Well-Being - Cho, Inn-Kyu; Lee, Jihoon; Kim, Kyumin; Lee, Joohee; Lee, Sangha; Yoo, Soyoung; Suh, Sooyeon; Chung, Seockhoon (Frontiers in Psychiatry, 2021)
Objectives: In the current coronavirus disease (COVID-19) pandemic, schoolteachers experience stress from addressing students or performing school tasks that may result in burnout. This study aimed to observe whether teachers' stress and anxiety due to the pandemic can influence their depression or psychological well-being and examine whether their resilience or self-efficacy mediates this association. Methods: During March 4–15, 2021, 400 teachers participated and responded voluntarily to an online survey that included the Stress and Anxiety to Viral Epidemics-9 items (SAVE-9), the Teacher-Efficacy Scale, the Brief Resilience Scale (BRS), the WHO-5 Well-Being Index, and the Patients Health Questionnaire-9 items. Results: High psychological well-being of teachers in COVID-19 pandemic era was expected by a low SAVE-9 score (aOR = 0.95; 95% CI, 0.91–0.99), a high level of self-efficacy (aOR = 1.03; 95% CI, 1.01–1.06), and a high BRS score (aOR = 1.18; 95% CI, 1.10–1.27). Moreover, teachers' resilience mediated the effects of stress and anxiety from the COVID-19 pandemic on their subjective well-being or depression. Conclusions: Schoolteachers' subjective well-being and depression were influenced by high levels of stress and anxiety of the viral epidemic, and their resilience mediated this relationship in this COVID-19 pandemic era.